1987
DOI: 10.1161/01.res.60.5.780
|View full text |Cite
|
Sign up to set email alerts
|

Effects of increasing intercellular resistance on transverse and longitudinal propagation in sheep epicardial muscle.

Abstract: Propagation in cardiac muscle is faster in the longitudinal than in the transverse axis of the cells. Yet, as a result of the larger upstroke velocity of action potentials propagating transversely, it has been suggested that longitudinal propagation is more vulnerable to block. To study the relation between conduction velocity and maximal upstroke velocity (Vmax), as well as the time course of conduction delay and block in the transverse vs. longitudinal direction, thin square pieces of sheep epicardial muscle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
76
1
3

Year Published

1995
1995
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(89 citation statements)
references
References 14 publications
9
76
1
3
Order By: Relevance
“…The increase in upstroke velocity in transverse propagation results from higher resistivity and reduced space constant in this direction. Thus, less current is lost to the neighboring cells (Delmar et al, 1987).…”
Section: Source-sink Problemmentioning
confidence: 99%
“…The increase in upstroke velocity in transverse propagation results from higher resistivity and reduced space constant in this direction. Thus, less current is lost to the neighboring cells (Delmar et al, 1987).…”
Section: Source-sink Problemmentioning
confidence: 99%
“…In 12 hearts, reset curves were made during perfusion of the LAD with heptanol (0.75 mmol/L). Because at higher concentrations, heptanol also blocks the fast sodium channels, 25,26 termination of VT by higher concentrations of heptanol was not studied systematically.…”
Section: Experimental Protocolmentioning
confidence: 99%
“…This observation is difficult to explain by an increased junctional resistance alone. Some studies have suggested that changes in cell-tocell communication may also have an indirect effect on the action potential 25,42,43 and that heptanol may change the capacitance of the membrane. 39,43 Therefore, it remains uncertain whether the prolongation of the partially excitable period is due to electrical uncoupling alone or whether a change in availability or kinetics of the fast sodium channels may also play a role.…”
Section: Slow Conduction Due To Electrical Uncouplingmentioning
confidence: 99%
“…A este esquema se le conoce como partición Godunov y se puede demostrar que es orden uno en tiempo O( Alternativamente el problema (58) y (59) se puede resolver como: (62) Este esquema propuesto por Strang (1968) es orden dos en tiempo. Para aplicarlo al modelo monodominio, elegimos L1 como el operador asociado al término reactivo y L2 el operador asociado al término difusivo, ,…”
Section: Partición Del Operadorunclassified
“…El grupo de investigación de Delmar en 1987, investigaron la propagación longitudinal y transversal en las capas delgadas del músculo cardíaco en ovejas antes y después de su perfusión con heptanol, un agente que reduce el acoplamiento de los gap junctions. y descubrieron que la propagación transversal es más sensible al desacoplamiento indicando una caída del factor de seguridad en estas circunstancias (Delmar et al 1987). …”
Section: Método Simplificado De Remodelado De Gap Junctionsunclassified